Weakened Baroclinic Activity Causes an Abrupt Rise in Fog in the Indo‐Gangetic Plain. Issue 24 (21st December 2021) - Gunturu, Udaya Bhaskar; Kumar, Vinay
Abstract: Dense and widespread winter fog in the Indo‐Gangetic Plain (IGP) causes a significant reduction in visibility and worsened air pollution. Despite extensive observational campaigns, the key processes in the formation and persistence of fog are not yet clear. The global increase in surface temperatures led to a decline in the incidence of fog, whereas the IGP experienced a sudden increase in fog incidence. It is shown here that abruptly reduced activity of the western disturbances (WD) around 1996–1997 resulted in a sudden decline of the cloud cover in the region, with a concomitantly enhanced radiative cooling of the surface and the atmosphere. These abrupt changes, aided by the impacts of human activities, altered the dynamics and thermodynamics of the boundary layer to favor fog formation. Also, the critical role of the extensive deep subsidence in the modulation of stable stratification and turbulence, which are essential for fog formation, is elucidated. Plain Language Summary: Atmospheric subsidence stabilizes the atmospheric boundary layer in the Indo‐Gangetic Plain. Radiative cooling of the ground surface and the atmosphere further enhances the stable stratification and suppresses the turbulence. Western disturbances, which are baroclinic storms occurring in the IGP, cause formation of clouds in the middle and upper troposphere. A sudden decrease in their frequency and intensity since 1996–1997 resulted in reduced cloud cover in the middle and upper troposphere in the region, and hence enhanced radiative cooling of the surface and the atmosphere. The enhanced radiative cooling created dynamical and thermodynamic conditions favorable for fog formation. Increased irrigation of crops during winter in the region further favored saturation of the air closer to the ground. As a result, the incidence of fog increased since 1996–1997. Key Points: The boundary layer stability in the Indo‐Gangetic Plain is maintained by deep subsidence, and the radiative cooling in the winter A sudden decrease in the frequency and intensity of western disturbances enhanced cooling, and hence altered boundary layer physics Altered dynamics, thermodynamics, and increased irrigation enhanced formation of fog since 1996–1997